Tracking plasma cell differentiation and survival. Issue 1 (15th October 2013) - Roth, Katrin; Oehme, Laura; Zehentmeier, Sandra; Zhang, Yang; Niesner, Raluca; Hauser, Anja E.
Abstract Plasma cells play a crucial role for the humoral immune response as they represent the body's factories for antibody production. The differentiation from a B cell into a plasma cell is controlled by a complex transcriptional network and happens within secondary lymphoid organs. Based on their lifetime, two types of antibody secreting cells can be distinguished: Short‐lived plasma cells are located in extrafollicular sites of secondary lymphoid organs such as lymph node medullary cords and the splenic red pulp. A fraction of plasmablasts migrate from secondary lymphoid organs to the bone marrow where they can become long‐lived plasma cells. Bone marrow plasma cells reside in special microanatomical environments termed survival niches, which provide factors promoting their longevity. Reticular stromal cells producing the chemokine CXCL12, which is known to attract plasmablasts to the bone marrow but also to promote plasma cell survival, play a crucial role in the maintenance of these niches. In addition, hematopoietic cells are contributing to the niches by providing other soluble survival factors. Here, we review the current knowledge on the factors involved in plasma cell differentiation, their localization and migration. We also give an overview on what is known regarding the maintenance of long lived plasma cells in survival niches of the bone marrow. © 2013 International Society for Advancement of Cytometry